Comparative Phytochemical and Structural Characterization of Powder and Ethanolic Extract of Hedyotis diffusa - Pandi, Kaniga; Keerthivasan, Nimithasree; Saravanan, Mridula Dhanapal; Govindaraj, Dhanavarsha (Asian Journal of Chemistry, 2026)
The present investigation focuses on the comparative phytochemical and structural evaluation of Hedyotis diffusa in powder form and its ethanolic extract. A combination of phytochemical screening and analytical techniques, namely Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM), was utilized to examine their chemical composition and surface characteristics. FTIR analysis revealed the presence of important functional groups, including hydroxyl, carbonyl, and phenolic constituents, as indicated by prominent absorption bands at 3400 cm–1 (O–H stretching), 1635 cm–1 (C=O stretching), and 1050 cm–1 (C–O stretching). These groups are associated with potential involvement in metal ion interaction and stabilization mechanisms. The XRD pattern of the powdered sample exhibited well-defined diffraction peaks, confirming its semi-crystalline structure, while the ethanolic extract showed a predominantly amorphous profile due to the abundance of organic compounds. SEM observations indicated an irregular and finely textured surface morphology, which may contribute to increased surface activity. The comparative findings underscore notable differences between the two forms, offering valuable insight into their physico-chemical and functional properties.